2003
DOI: 10.1093/heapro/18.2.163
|View full text |Cite
|
Sign up to set email alerts
|

The ‘wonderfulness’ of children’s feeding programs

Abstract: When people involved in children's feeding programs were asked to describe them, without exception they were described using phrases that reflected the perception of 'wonderfulness'. This paper critically analyses the 'wonderfulness' of children's feeding programs by examining the language used to describe these programs, and the features of a 'wonderful' program through an analysis of a multi-site, qualitative case study of nine diverse programs in Atlantic Canada. When participants justified their comments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although several studies have assessed the quantitative outcomes of school feeding programmes, studies on the perceptions and expectations of a feeding programme using qualitative data are rare (Williams, McIntyre, Dayle & Raine, 2003). Williams and his colleagues argued that most of the studies were focused on nutritional outcomes rather than the perceptions of the people involved in the intervention.…”
Section: Perception Of Community Members About the School Feeding Promentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have assessed the quantitative outcomes of school feeding programmes, studies on the perceptions and expectations of a feeding programme using qualitative data are rare (Williams, McIntyre, Dayle & Raine, 2003). Williams and his colleagues argued that most of the studies were focused on nutritional outcomes rather than the perceptions of the people involved in the intervention.…”
Section: Perception Of Community Members About the School Feeding Promentioning
confidence: 99%
“…Research has also shown that stakeholders hold varied perceptions about the school feeding programme. While some stakeholders held the programme in high esteem, because their livelihoods depended on the success of the programme (Williams, McIntyre, Dayle, & Raine, 2003), other community members expected more involvement in order to improve the outcomes of the school feeding intervention (Pappas et al, 2008). In another study, community members requested for the need to high qualified cooks, increase use of locally produced foods and the attachment of school farms to existing school feeding programmes (Quaye, Essegbey, Frempong, & Ruivenkamp, 2010).…”
Section: Perception Of Community Members About the School Feeding Promentioning
confidence: 99%
“…30 A decrease in food variety may also occur as families utilize strategies to make their food purchases last longer, which may include diluting milk and juice purchases to extend the life of these products for their children. 13,31 The fact that food-insecure households seem to rely of late more on internal coping strategies might indicate that food insecurity and specifically, child hunger, are increasingly regarded as private matters that should stay within family boundaries. It has been previously shown that food-insecure households in Canada more often choose to compromise their nutrition by eating cheaper foods (46%) and skipping meals or eating less (28%), rather than receive food from charity (22%).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Canadian research suggests that these community-based programs threaten to mask the necessity of federally funded poverty reduction strategies, 3,21 just as their innate "wonderfulness" may mask other negative impacts 22 such as perpetuating health inequalities and disempowering parents. 18,22,23 The…”
Section: School Food In Canada and The United Statesmentioning
confidence: 99%
“…It is not clear whether school gardens are prone to the same challenges as other ad hoc community-based feeding programs3,16,18,[21][22][23] or if they can be effective in contributing to longer term, systemic changes to food systems.…”
mentioning
confidence: 99%